Using modeling to understand how athletes in different disciplines solve the same problem: Swimming versus running versus speed skating - de Koning, J. J.; Foster, C.; Lucia, A.; Bobbert, M. F.; Hettinga, F. J.; Por, J. P. (International Journal of Sports Physiology and Performance, 2011)
Every new competitive season offers excellent examples of human locomotor abilities, regardless of the sport. As a natural consequence of competitions, world records are broken every now and then. World record races not only offer spectators the pleasure of watching very talented and highly trained athletes performing muscular tasks with remarkable skill, but also represent natural models of the ultimate expression of human integrated muscle biology, through strength, speed, or endurance performances. Given that humans may be approaching our species limit for muscular power output, interest in how athletes improve on world records has led to interest in the strategy of how limited energetic resources are best expended over a race. World record performances may also shed light on how athletes in different events solve exactly the same problem—minimizing the time required to reach the finish line. We have previously applied mathematical modeling to the understanding of world record performances in terms of improvements in facilities/equipment and improvements in the athletes` physical capacities. In this commentary, we attempt to demonstrate that differences in world record performances in various sports can be explained using a very simple modeling process.